Pemetaan Batimetri dan Analisis Morfometri untuk Evaluasi Kondisi Fisik Wisata Danau Perintis, Bone Bolango - La Ode Juni Akbar; Bambang Djau; Dewi Sartika T. Zees (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
The objective of this study is to conduct bathymetric mapping and morphometric analysis to evaluate the physical condition of Perintis Lake, Bone Bolango. This research employs a descriptive quantitative approach, utilizing survey methods and field observations. Bathymetric mapping was performed using the Underwater Meter Gauge method, with data interpolation analyzed through the Spline with Barriers method in ArcMap. Lake morphometry was assessed by calculating surface and subsurface dimensions based on bathymetric data. The results of the bathymetric and morphometric analyses reveal that Perintis Lake is a shallow water body (average depth of 1.88 m) with complex morphological characteristics. A Shoreline Development Index (SDI) of 1.84 indicates an irregular lake shape with diverse littoral habitats, while an aspect ratio of 4.02 reflects a suboptimal unidirectional water circulation pattern. Morphometric characteristics, such as a Volume Development Value of 1.61 and a Zmax/Zmean ratio of 1.87, suggest high susceptibility to sedimentation, unstable thermal stratification, and organic sediment accumulation. The study highlights the need for an ecologically zoned management approach, including sediment input control, littoral zone conservation, and periodic bathymetric monitoring to ensure the sustainability of Perintis Lake's ecosystem.